Ein Fachverband für Krankenhausseelsorge und Spiritual Care im Gesundheitswesen: Werkstattbericht aus der Konferenz für Krankenhausseelsorge in der EKD - Dreher, Thomas (Wege zum Menschen, 2025)
This report reflects on a work in progress: the Conference for Hospital Chaplaincy in the Protestant Church of Germany (EKD)'s new Professional Association for Chaplaincy and Spiritual Care in the Health Care System. This association addresses the growing cuts in hospital chaplaincy in the German Protestant mainline churches and a more secularized society. A professional association can improve chaplaincy quality, communication, and adaptability in a changing society and healthcare.